Effects of peat derived humic acid on ammonia volatilization from urea fertilizer - Lee, Jia Huey (2011)
There are about 2.7 million hectares of peat swamps in Malaysia, which account for 8% of the country’s total area. 1.7 million hectares are in Sarawak (63%). Peats are well-known for their high organic matter. For instance, humic matter can be further categorized into humin, fulvic and humic acids. Being organic in nature, humic acid is an ideal material to be mixed with ammonium and potassium to produce organically amended fertilizer. However, there are several factors that limit the production of the fertilizer mentioned above. For instance, extraction of humic acids is a time consuming process. Furthermore, type and concentration of extractant also influence the yield of humic acids. These information are critical in the study of humic acids but they are lacking for humic acids isolated from Sarawak peat. Hence, first part of this study was to investigate the effect of different levels of extractant concentration on the yield of humic acid extracted from Sarawak peat soil (saprists). Modified standard procedure was adopted by using six different concentrations of NaOH and KOH to extract humic acid. Results showed that there was a linear relationship between levels of concentrations and yield of humic acid and the concentration that gave optimum yield was 0.5 M. In terms of economics, this finding might be useful especially in large scale isolation of humic acids from tropical peats. As humic acids contain quinone that could function as urease inhibitor, humic acids are useful in reducing ammonia loss from urea. However, limited information is known regarding effect of humic acids isolated from Sarawak peat on ammonia volatilization. Hence, the objective of second part of the study was to evaluate the effect of peat derived humic acid on ammonia volatilization from urea. Effectiveness of the organically amended urea was evaluated under laboratory condition. Ten treatments namely, urea (liquid), 0.5 M KOH, urea + 0.5 M KOH, urea + humic acid without purification (0.75, 1.00 and 4.00 g), urea + humic acid purified once (0.75, 1.00 and 4.00 g) and control (soil alone) were used in this study with the aim of reducing nitrogen loss from urea. A closed dynamic air flow system was used to estimate nitrogen loss from soil. A 250 g of mineral soil at field capacity (60% moisture content) was used. The amounts of ammonia loss from the applied treatments were evaluated daily where the ammonia collected in boric acid was titrated with 0.01 M HCl every 24 hours until the loss decreased to less than 0.1%. Similar experiment was also set up in order to determine the actual time of ammonium and nitrate retention in soil. At the end of the fertilizer evaluation, soil samples were analyzed for pH (water and KCl), ammonium and nitrate contents. Results showed that the use of 4.00 g of humic acids significantly reduced ammonia volatilization. Treatments with humic acid also showed significantly higher amount of exchangeable ammonium and available nitrate compared to treatments without humic acid. However, there was no significant difference between humic acid without purification and humic acid purified once. This suggests that purification could be ignored if large scale extraction of humic acids is to be done. Apart from reducing the time needed to obtain humic acid, the outcome of this study will also help to reduce their production cost.